Modden: An Integrated Approach for Model Driven Development and Software Product Line Processes - Magalhaes, Ana Patrícia; David, Jose Maria N.; Maciel, Rita Suzana P.; Silva, Bruno Carreira; Silva, Filipe Araujo da (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
In a Software Product Line reuse should be considered from the artifacts conception stage and, when implemented, these artifacts can be part of a library to be further reused by every domain application. In a model-driven context an application development can be seen as a set of transformations that lead to a final system. However, during the transformation process reuse techniques are not usually considered. Modden is a SPL approach that uses model-driven techniques. Through the integration of these two approaches we aim to enhance model-driven techniques by the reuse of models, code, transformation rules and so on. As a result, Modden aims to leverage the reuse of these artifacts in different software development process phases. It comprises two processes, one to develop core assets and another to develop specific assets for the product line, a SPL UML profile and a model driven development supporting tool.